Change and the politics of certainty - Edkins, Jenny (Manchester University Press, 2019)
Despite the imperative for change in a world of persistent inequality, racism, oppression and violence, difficulties arise once we try to bring about a transformation. As scholars, students and activists, we may want to change the world, but we are not separate, looking in, but rather part of the world ourselves. The book demonstrates that we are not in control: with all our academic rigour, we cannot know with certainty why the world is the way it is, or what impact our actions will have. It asks what we are to do, if this is the case, and engages with our desire to seek change. Chapters scrutinise the role of intellectuals, experts and activists in famine aid, the Iraq war, humanitarianism and intervention, traumatic memory, enforced disappearance, and the Grenfell Tower fire, and examine the fantasy of security, contemporary notions of time, space and materiality, and ideas of the human and sentience. Plays and films by Michael Frayn, Chris Marker and Patricio Guzmán are considered, and autobiographical narrative accounts probe the author's life and background. The book argues that although we might need to traverse the fantasy of certainty and security, we do not need to give up on hope.